Bone marrow mesenchymal stem cells from infants with MLL-AF4(+) acute leukemia harbor and express the MLL-AF4 fusion gene - Menendez, Pablo (The Rockefeller University Press, 2009)
MLL-AF4 fusion is a hallmark genetic abnormality in infant B-acute lymphoblastic leukemia (B-ALL) known to arise in utero. The cellular origin of leukemic fusion genes during human development is difficult to ascertain. The bone marrow (BM) microenvironment plays an important role in the pathogenesis of several hematological malignances. BM mesenchymal stem cells (BM-MSC) from 38 children diagnosed with cytogenetically different acute leukemias were screened for leukemic fusion genes. Fusion genes were absent in BM-MSCs of childhood leukemias carrying TEL-AML1, BCR-ABL, AML1-ETO, MLL-AF9, MLL-AF10, MLL-ENL or hyperdiploidy. However, MLL-AF4 was detected and expressed in BM-MSCs from all cases of MLL-AF4(+) B-ALL. Unlike leukemic blasts, MLL-AF4(+) BM-MSCs did not display monoclonal Ig gene rearrangements. Endogenous or ectopic expression of MLL-AF4 exerted no effect on MSC culture homeostasis. These findings suggest that MSCs may be in part tumor-related, highlighting an unrecognized role of the BM milieu on the pathogenesis of MLL-AF4(+) B-ALL. MLL-AF4 itself is not sufficient for MSC transformation and the expression of MLL-AF4 in MSCs is compatible with a mesenchymal phenotype, suggesting a differential impact in the hematopoietic system and mesenchyme. The absence of monoclonal rearrangements in MLL-AF4(+) BM-MSCs precludes the possibility of cellular plasticity or de-differentiation of B-ALL blasts and suggests that MLL-AF4 might arise in a population of prehematopoietic precursors.